Sperm DNA Fragmentation and Sperm-Borne miRNAs: Molecular Biomarkers of Embryo Development? - Conflitti, Anna Chiara; Cicolani, Gaia; Buonacquisto, Alessandra; Pallotti, Francesco; Faja, Fabiana; Bianchini, Serena; Blaconà, Giovanna; Bruno, Sabina Maria; Linari, Antonella; Lucarelli, Marco; Montanino, Diletta; Muzii, Ludovico; et al. (International journal of molecular sciences, 2023)
The evaluation of morpho-functional sperm characteristics alone is not enough to explain infertility or to predict the outcome of Assisted Reproductive Technologies (ART): more sensitive diagnostic tools are needed in clinical practice. The aim of the present study was to analyze Sperm DNA Fragmentation (SDF) and sperm-borne miR-34c-5p and miR-449b-5p levels in men of couples undergoing ART, in order to investigate any correlations with fertilization rate, embryo quality and development. Male partners (n = 106) were recruited. Semen analysis, SDF evaluation and molecular profiling analysis of miR-34c-5p and miR-449b-5p (in 38 subjects) were performed. Sperm DNA Fragmentation evaluation- a positive correlation between SDF post sperm selection and the percentage of low-quality embryos and a negative correlation with viable embryo were found. SDF > 2.9% increased the risk of obtaining a non-viable embryo by almost 4-fold. Sperm miRNAs profile—we found an association with both miRNAs and sperm concentration, while miR-449b-5p is positively associated with SDF. Moreover, the two miRNAs are positively correlated. Higher levels of miR-34c-5p compared to miR-449b-5p increases by 14-fold the probability of obtaining viable embryos. This study shows that SDF, sperm miR-34c-5p, and miR-449b-5p have a promising role as biomarkers of semen quality and ART outcome.